2003
DOI: 10.3998/ark.5550190.0004.a16
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new aldehyde derivatives from β-lapachone and nor-β-lapachone

Abstract: Derivatives 6a and 6b, have been obtained in a chemoselective manner by a two step synthesis from β-lapachone (3a) and nor-β-lapachone (3b), respectively, using CH 2 N 2 in ether, which provided the lapachone-epoxide derivatives, 5a and 5b, followed by treatment with BF 3 .Et 2 O/CH 2 Cl 2 . Basic work-up of the reaction mixture of 5a or 5b with BF 3 .Et 2 O/CH 2 Cl 2 led instead to isolation of the rearranged derivatives 7a and 7b, respectively. An ab initio theoretical study [B3LYP/6-311+G(d)] on 3a indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The available literature confirmed that there is a strong correlation between nutrients, photosynthesis and secondary metabolite production. Plants such as Alstonia extracts obtained from these plants were used to treat many ailments such as fever, malaria [33], tumors [34], asthma [35], antidiabetic [36] and antioxidant [37]; antitumor activity, antimetastatic activity anti-microbial and antifungal activity [38,39], antiviral activity [40], anti-inflammatory [41], antiparasitic activity [42], leishmanicidal activity [43]and molluscicidal activity [44];…”
mentioning
confidence: 99%
“…The available literature confirmed that there is a strong correlation between nutrients, photosynthesis and secondary metabolite production. Plants such as Alstonia extracts obtained from these plants were used to treat many ailments such as fever, malaria [33], tumors [34], asthma [35], antidiabetic [36] and antioxidant [37]; antitumor activity, antimetastatic activity anti-microbial and antifungal activity [38,39], antiviral activity [40], anti-inflammatory [41], antiparasitic activity [42], leishmanicidal activity [43]and molluscicidal activity [44];…”
mentioning
confidence: 99%
“…The antitumor activity of lapachol may be due to its interaction with nucleic acids and the interaction of the naphthoquinone moiety between base pairs of the DNA helix occurs with subsequent inhibition of DNA replication and RNA synthesis [4]. Other biological activities of lapachol are antimetastatic activity [5], antimicrobial and antifungal activity [6], antiviral activity [7], anti-inflammatory [8], antiparasitic activity [4], leishmanicidal activity [9] and molluscicidal activity [10].…”
Section: Introductionmentioning
confidence: 99%